2014
DOI: 10.2214/ajr.13.11023
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Based Ratio of Fetal Lung Volume to Fetal Body Volume as a New Prognostic Marker in Congenital Diaphragmatic Hernia

Abstract: In our study, the MRI-based FLV/FBV ratio was able to predict neonatal survival and ECMO requirement in children with CDH with high accuracy. Unlike other prognostic parameters, FLV/FBV ratio is independent of a reference to a control group and may enhance prognostic accuracy particularly in growth-restricted neonatal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Only once a comprehensive assessment has been made can multidisciplinary prenatal counseling by clinicians in tertiary centers be offered to inform parents about the estimated prognosis after birth. Several other additional imaging methods, such as lung volumetry, 3D ultrasound and Doppler studies of the pulmonary vascularization, have been shown in individual series to be prognostic for pulmonary hypertension, the need for extracorporeal membrane oxygenation (ECMO) and survival [8]. All of these remain research tools, however, but may ultimately improve the predictive value of prenatal testing.…”
Section: Resultsmentioning
confidence: 99%
“…Only once a comprehensive assessment has been made can multidisciplinary prenatal counseling by clinicians in tertiary centers be offered to inform parents about the estimated prognosis after birth. Several other additional imaging methods, such as lung volumetry, 3D ultrasound and Doppler studies of the pulmonary vascularization, have been shown in individual series to be prognostic for pulmonary hypertension, the need for extracorporeal membrane oxygenation (ECMO) and survival [8]. All of these remain research tools, however, but may ultimately improve the predictive value of prenatal testing.…”
Section: Resultsmentioning
confidence: 99%
“…Basierend einerseits auf De Paepe et al [11], die post mortem mit dem Quotienten aus Lungen-zu Körpergewicht den Grad der Lungenhypoplasie bestimmten und andererseits durch die verlässliche Vorhersage der Lungenhypoplasie durch den Quotienten aus MR-FLV und sonografisch bestimmtem fetalem Gewicht [34], entstand die Idee zur Betrachtung des Quotienten aus FLV/FBV mittels MRT-Volumetrie. Weidner et al haben gezeigt, dass der Quotient im Hinblick auf Überleben (AUC 0,829) und ECMO-Bedarf (AUC 0,811) als hochwertiger prognostischer Parameter einzustufen und mit bereits etablierten Parametern hinsichtlich der prognostischen Wertigkeit vergleichbar ist [36].…”
Section: Hintergrundunclassified
“…Several teams have reported their experience with prediction of outcome using either ultrasound or magnetic resonance imaging, based on lung measurement and liver or stomach position. However, there are inadequate numbers in these studies to truly demonstrate whether these are independent predictors of outcome . Although tracheal occlusion for CDH may reduce mortality (and apparently also early neonatal morbidity), it should be still considered investigational.…”
Section: Advances In Fetal Surgerymentioning
confidence: 99%